Quartz natural and laboratory ESR dose response curves: A first attempt from Chinese loess. (15th December 2018) - Tsukamoto, Sumiko; Long, Hao; Richter, Marcus; Li, Yan; King, Georgina E.; He, Zhong; Yang, Linhai; Zhang, Jingran; Lambert, Renske
Abstract: The natural electron spin resonance (ESR) dose response curve (DRC) of the Al and Ti centres was constructed for the first time using sand-sized quartz samples from Luochuan, Chinese Loess Plateau. The natural DRC of both centres showed an unexpected early saturation, with characteristic saturation dose ( D 0 ) values of ∼760 Gy for the Al centre and ∼650 Gy for the Ti centre, when fitted with a single saturating exponential function. This corresponds to an upper age limit of ∼500 ka (Al centre) and ∼400 ka (Ti centre), using the mean dose rate of 3 Gy/ka. The laboratory DRC of both centres showed much higher saturation dose, but both intensity and D 0 value of the regenerated ESR signals decreased significantly with increasing preheat temperatures. The natural DRC had a better match with the laboratory DRC following higher temperature preheats, ∼210–240 °C for 4 min, suggesting the need for preheating after laboratory irradiation for quartz ESR dating. The results of isothermal heating tests revealed that the thermal lifetime at 10 °C at the studied site was ∼1.5 × 10 9 and ∼1.7 × 10 6 years for the Al and Ti centres. Although the thermal lifetime of these impurity centres could be sample dependent, the relatively short lifetime of the Ti centre contributed to the early saturation of the natural DRC of the Chinese loess. This highlights the importance of investigating the thermal lifetime of signals for dating older samples using ESR. Highlights: Upper dating limit of quartz ESR dating is assessed by the natural dose response of Al and Ti centres. The natural dose response curve is compared with the laboratory dose response curve. The impact of preheating, bleaching and thermal lifetime on the dose response curve is investigated.